Grafting of silane and graphene oxide onto PBO fibers: Multifunctional interphase for fiber/polymer matrix composites with simultaneously improved interfacial and atomic oxygen resistant properties. (16th January 2015) - Chen, Lei; Wei, Feng; Liu, Li; Cheng, Weilu; Hu, Zhen; Wu, Guangshun; Du, Yunzhe; Zhang, Chunhua; Huang, Yudong
Abstract: Atomic oxygen (AO) is a dominant component of the low earth orbit and can erode most spacecraft materials. In this work, both silane and graphene oxide (GO) were introduced onto poly( p -phenylene benzobisoxazole) (PBO) fibers to prevent AO from penetrating into the interface of PBO fiber/epoxy composites. The microstructure, mechanical properties and AO erosion resistance of PBO fibers before and after modification were investigated. Experimental results revealed that the GO was successfully grafted onto PBO fibers using 3-aminopropyltrimethoxysilane (APTMS) as the bridging agent. The surface roughness ( R a ) and wettability of the obtained hybrid fibers (PBO–APTMS–GO) were obviously increased in comparison with those of an untreated one. In addition, PBO–APTMS–GO showed simultaneously remarkable enhancement in interfacial shear strength (IFSS) and AO erosion resistance. Meanwhile, single filament tensile strength (TS) had no obvious decrease after the grafting processes. We believe the facile and effective method may provide a novel interface design strategy for developing multifunctional fibers.